Analisis Faktor Internal Dan Eksternal Yang Mendorong UMKM Naik Kelas: Pendekatan Systematic Literature Review - Siera Syailendra; Mira Tasya Rahma Dani; Ramado Anuar; Sopian; Abdullah Rasjid; Biocella Viona Avisha; Purnama Rinif (Journal of Economics and Business, 2026)
This study aims to analyze internal and external factors influencing MSMEs' upgrading based on previous research findings. The method used is a Systematic Literature Review (SLR) with stages of inquiry, literature search, article screening, feasibility assessment, and thematic synthesis. The results of the study indicate that internal factors—entrepreneurial capacity, innovation, and resource management—and external factors—policy support, access to financing, and the business ecosystem—play a significant role in encouraging MSMEs to upgrade. While the synergy of these two factors is key, internal factors are the primary determinant of MSME success. This study provides a conceptual contribution in strengthening the understanding of the determinants of MSME upgrading through a systematic synthesis of previous research